Corrective Osteotomies for Complex Intra-Articular Tibial Plateau Malunions using Three-Dimensional Virtual Planning and Novel Patient-Specific Guides - Wang, Huixiang; Newman, Simon; Wang, Jiandong; Wang, Qian; Wang, Qiugen (The Journal of Knee Surgery, 2018)
Corrective osteotomy of intra-articular tibial plateau malunions is technically demanding for orthopaedic surgeons. The aim of our study was to evaluate the feasibility of the combination of three-dimensional (3D) virtual planning and novel patient-specific guides for assisting correction of complex intra-articular tibial plateau malunions. Six patients with posttraumatic intra-articular tibial plateau malunions were included. Preoperatively 3D models of the tibias were reconstructed using the computed tomography scan data. Virtual surgical planning was performed, and patient-specific guides for osteotomy and reduction were designed, which were then 3D printed. Intraoperatively they were applied to guide the osteotomy and reduction. After surgery, radiographs were taken to evaluate the knee joint surface. The operating surgeons were asked to complete the Likert scale questionnaire to assess their attitude to the novel technology. The guides were successfully used for guiding osteotomy correction of malunion in all patients. Postoperative radiographs showed the articular step-off was considerably reduced and the articular congruency was satisfactory in all patients. The results of the questionnaire demonstrated a high level of surgeon satisfaction and acceptance to the technology. For selective patients with complex intra-articular tibial plateau malunions, the novel technique could serve as a valuable option for guiding precise malunion correction.
Keywords: surgical plan; patient-specific guide; tibial plateau fracture malunion; osteotomy